The valor of ignorance - Lea, Homer (Harper & brothers, 1909)
One of the foremost strategists of the American Army in the first decade of the twentieth century warns of the great danger of militarized Japan and forcasts -- 44 years before it actually happened -- the Japanese invasion of the Philippines.